Knowledge and attitude towards digital pharmacy of pharmacists in Serbia - Tatić, Natalija; Stojkov, Svetlana; Jocić, Dragana; Jovanović Lješković, Nataša (Archives of Pharmacy, 2022)
Pandemic COVID caused significant increase in digital healthcare technologies (DHT) utilisation. Since a potential hindrance to their further adoption may the healthcare professionals’ receptivity, pharmacists’ knowledge and attitudes towards the technologies were investigated in Serbia. Cross sectional study was conducted through a purposefully created and voluntarily and anonymously self-reported online survey. Out of 119 participants, 87% were pharmacists working in a pharmacy, 7% in teaching, science and other branches, while 6% were pharmaceutical technicians. Uninformed or incorrect was on average 86% of the participants about digital medicines and 90% about digital therapeutics. “Natural cycles” was recognized by 25% of the participants. However, the average of 66% thought DHT could help healthcare professionals and patients in health preservation, diagnosis and therapy, while 25% were undecided. This could indicate a lack of pharmacists’ exposure to information, rather than the previously described mistrust towards DHT. Only 13% of the participants were uninterested to learn more about the various aspects of digital pharmacy, which may support the hypothesis. A significantly higher number of participants, 66%, was familiar with telemedicine. Despite its expansion caused by the pandemic, 74% of the participants labelled direct contact with patients as “very important”. This may impede telemedicine application to pharmaceutical healthcare, notwithstanding that 47% wanted to learn more about telemedicine. The results indicated potential openness towards the utilisation, as well as the lack of education on DHT, with the exception of telemedicine.